Consideration of a family case of X-linked hypophosphatemia through the prism of modern diagnostic and treatment methods - L.I. Vakulenko (Počki)
Background. X-linked hypophosphatemia is the most common form of hereditary vitamin D-resistant rickets. Today, there is a late diagnosis, later treatment start and a significant deterioration in the quality of life of patients with X-linked hypophosphatemia. The aim of the study is to use a clinical case as an example in order to draw attention to the problem of X-linked hypophosphatemia and consider traditional and novel approaches to the diagnosis and therapy. Materials and methods. We analyzed a family case of X-linked hypophosphatemia in a 4-year-old boy. Results. Based on the analysis of a family case, modern approaches to clinical, laboratory and instrumental diagnosis recommended by international clinical guidelines for the diagnosis and treatment of X-linked hypophosphatemia are considered. The causes for late diagnosis, advantages and disadvantages of traditional therapy are analyzed. Treatment was adjusted including phosphate and active vitamin D preparations, taking into account international clinical guidelines. The latest data are presented on the treatment of X-linked hypophosphatemia with biological therapy using burosumab. The results of short-term studies on the efficacy and safety of burosumab in children and adults are described. Conclusions. X-linked hypophosphatemia is a complex hereditary tubulopathy requiring timely diagnosis, treatment and thorough patient management by a multidisciplinary team of doctors. Once X-linked hypophosphatemia is suspected, a clinical, laboratory and instrumental examination of a patient should be carried out in accordance with international recommendations. Although traditional therapy has limited therapeutic efficacy and side effects, its early initiation is associated with better outcomes. A significant progress in the treatment of hypophosphatemic vitamin D-resistant rickets was achieved due to the biological therapy with burosumab aimed at its pathophysiological mechanisms. The profile of burosumab effects allows this therapy to be considered life-saving.